2021
DOI: 10.1007/s11881-021-00246-w
|View full text |Cite
|
Sign up to set email alerts
|

The effect of audio-support on strategy, time, and performance on reading comprehension in secondary school students with dyslexia

Abstract: The use of adequate reading comprehension strategies is important to read efficiently. Students with dyslexia not only read slower and less accurately, they also use fewer reading comprehension strategies. To compensate for their decoding problems, they often receive audio-support (narration written text). However, audio-support linearly guides readers from beginning to end through texts, possibly hindering the use of reading comprehension strategies in expository texts and negatively impacting reading time an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…This has the important implication for the CTML that the impact of audio seems to differ between learners. The present results, combined with Knoop-van Campen et al (2022) who showed that audio support has a negative effect on students' reading comprehension strategy, indicate that information processing is active and that audio can reduce the number of reader-initiated actions: audio seem to make learning less active. For optimal learning, a learner must actively engage in the material (Caccamise et al, 2015).…”
Section: Navigation Strategies In Multimedia Learningsupporting
confidence: 65%
See 4 more Smart Citations
“…This has the important implication for the CTML that the impact of audio seems to differ between learners. The present results, combined with Knoop-van Campen et al (2022) who showed that audio support has a negative effect on students' reading comprehension strategy, indicate that information processing is active and that audio can reduce the number of reader-initiated actions: audio seem to make learning less active. For optimal learning, a learner must actively engage in the material (Caccamise et al, 2015).…”
Section: Navigation Strategies In Multimedia Learningsupporting
confidence: 65%
“…This fits with the statement that self-regulated learning is a "dynamic and developing process" (Boekaerts & Corno, 2005, p. 208). In addition, a recent study on multimedia and reading strategies in secondary school students showed that audio support had a negative effect on students' reading comprehension strategy (Knoop-van Campen et al, 2022). In this study, we found that audio elicited less efficient reading behavior: students made less reader-initiated decisions but tend to follow the audio.…”
Section: Navigation In Multimedia Learning Environmentsmentioning
confidence: 41%
See 3 more Smart Citations